Up-scalable emerging energy conversion technologies enabled by 2D materials: from miniature power harvesters towards grid-connected energy systems. Issue 6 (19th May 2021) - Rogdakis, Konstantinos; Karakostas, Nikolaos; Kymakis, Emmanuel
Abstract : Emerging energy harvesters enabled by 2D materials distributed across different locations of an energy sustainable city, providing power for miniature IoT devices and contributing in on-grid electricity generation. Abstract : Breakthrough discoveries in high-throughput formulation of abundant materials and advanced engineering approaches are both in utter need as prerequisites for developing novel large-scale energy conversion technologies required to address our planet's rising energy demands. Nowadays, the rapid deployment of Internet of Things (IoT) associated with a distributed network of power-demanding smart devices, concurrently urges for miniaturized systems powered by ambient energy harvesting. Graphene and other related two-dimensional materials (GRM) consist a perfect fit to drive this innovation owing to their extraordinary optoelectronic, physical and chemical properties that emerge at the limit of two-dimensions. In this review, after a critical analysis of GRM's emerging properties that are beneficial for power generation, novel approaches are presented for developing ambient energy conversion devices covering a wide range of scales. Notable examples vary from GRM-enabled large-scale photovoltaic panels and fuel cells, smart hydrovoltaics and blue energy conversion routes, to miniaturized radio frequency, piezoelectric, triboelectric, and thermoelectric energy harvesters. The insights from this review demonstrate that GRM-enabled energy harvesters, apart from enabling the self-powered operation of individual IoT devices, have also the potential to revolutionize the way that grid-electricity is provided in the cities of the future. This approach is materialized by two complementary paradigms: cross-coupled integration of GRM into firstly, a network consisted of a vast number of miniaturized, in-series-connected harvesters and secondly, into up-scaled, multi-energy hybrid harvesters, both approaches having the potential for on-grid energy generation under all-ambient-conditions. At the end of the discussion, perspectives on the trends, limitations and commercialisation potential of these emerging, up-scalable energy conversion technologies are provided. This review aims to highlight the importance of building a network of GRM-based, cross-scaled energy conversion systems and their potential to become the guideline for the energy sustainable cities of the future.